2009
DOI: 10.1029/2009gl038294
|View full text |Cite
|
Sign up to set email alerts
|

Soil n‐alkane δ13C along a mountain slope as an integrator of altitude effect on plant species δ13C

Abstract: Carbon isotopic compositions of leaf wax‐derived n‐alkanes (δ13Cwax) and bulk organic matter (δ13CSOM) in surface soils from ca. 1000 to 3800 m above sea level along Mount Gongga, China were investigated for their altitudinal variations. There is a breakpoint, suggesting a precipitation threshold, at 2050 m in both δ13Cwax and δ13CSOM trends. Above the threshold, δ13Cwax and δ13CSOM increase in a similar pattern of the average species‐level response to altitude reported from various humid mountainous areas. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
(70 reference statements)
1
15
0
Order By: Relevance
“…Aridity leads to closure of stomata to limit transpiration, with attendant 13 C-enrichment (Cernusak et al, 2013). Thus, δ 13 C is confounded in profiles where aridity is a variable (Friend et al, 1989, Wei andJia, 2009) but not in wet catchments, such as this one and that reported by Körner et al (1991). The addition of another elevation-sensitive proxy, and especially the ability to measure two isotope systems (δ 13 C and δD) in the same leaf wax molecules, offers the possibility to cross-check aridity effects (positive correlation) versus altitude effects (negative correlation).…”
Section: Paleoaltimetrymentioning
confidence: 99%
“…Aridity leads to closure of stomata to limit transpiration, with attendant 13 C-enrichment (Cernusak et al, 2013). Thus, δ 13 C is confounded in profiles where aridity is a variable (Friend et al, 1989, Wei andJia, 2009) but not in wet catchments, such as this one and that reported by Körner et al (1991). The addition of another elevation-sensitive proxy, and especially the ability to measure two isotope systems (δ 13 C and δD) in the same leaf wax molecules, offers the possibility to cross-check aridity effects (positive correlation) versus altitude effects (negative correlation).…”
Section: Paleoaltimetrymentioning
confidence: 99%
“…δ 13 C wax of C 4 plants in a transect in Cameroon show no correlation with rainfall or humidity (Garcin et al, ). Soil δ 13 C wax from the Cameroon transect shows a weak significant correlation with relative humidity (Schwab et al, ), and those from a transect in China show an altitude effect similar to that in bulk δ 13 C (Wei & Jia, ). Whether these finding are applicable to regions beyond those studied is something we investigate here.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the central physiological adaptations to dry ecosystems and to high altitudes (i.e. low leaf nitrogen-use efficiency and high water-use efficiency) are similar and such adaptations are demonstrated in gradient studies of Tibetan vegetation Wei and Jia, 2009). Experimental and modelling investigations have shown that plant-growth response to elevated CO 2 concentrations is amplified in vegetation types with high nitrogen but limited water supply McMurtrie et al, 2008).…”
Section: Changes In Atmospheric Co 2 Concentration As the Driving Formentioning
confidence: 99%
“…However, the photosynthetic capacity of alpine plants is not correspondingly lowered, probably as a result of physiological adaptation and acclimation, thereby accepting higher energetic costs to compensate for the low efficiency of physiological processes at high altitudes (Reich and Oleksyn, 2004). High-alpine plants have high leaf nitrogen concentrations indicating lower plant nitrogen-use efficiency (for the Tibetan Plateau, see He et al, 2006) and low water-use efficiency (Körner et al, 1988; for Tibetan Plateau, see Wei and Jia, 2009). Thus plants with xeromorphic leaf anatomies such as increased stomatal densities (Pyankov and Kondrachuk, 2003) are at a competitive advantage.…”
Section: Changes In Atmospheric Co 2 Concentration As the Driving Formentioning
confidence: 99%